Deep Instability in the Phylogenetic Backbone of Heteroptera is Only Partly Overcome by Transcriptome-Based Phylogenomics. Issue 6 (11th November 2019) - de Moya, Robert S; Weirauch, Christiane; Sweet, Andrew D; Skinner, Rachel K; Walden, Kimberly K O; Swanson, Daniel R; Dietrich, Christopher H; Johnson, Kevin P
Abstract: Heteroptera is a diverse suborder of insects that includes many plant pests, human disease vectors, and nuisance pests, but also beneficial insects. Previous analyses have supported recognition of seven monophyletic infraorders. A clade comprising Leptopodomorpha, Pentatomomorpha, and Cimicomorpha is also well-accepted, but relationships among the early-diverging lineages, including the aquatic infraorders (Nepomorpha and Gerromorpha), have remained poorly resolved and controversial. Phylogenomic analyses of 2, 159 gene alignments derived from Illumina sequencing of transcriptomes were employed to explore the stability of relationships among major heteropteran lineages. These analyses included maximum likelihood analyses of amino acid and nucleotide sequences, as well as multi-species coalescent analysis and quartet sampling. All analyses favored a sister position of the Nepomorpha to the remaining Heteroptera. The placement of the Nepomorpha and other ambiguously supported nodes, including some within the Pentatomomorpha were explored with quartet sampling. Results of quartet sampling revealed only a slight majority of quartets supported the placement of the Nepomorpha, and some varying alternate topologies were supported within the Pentatomomorpha. These results highlight the instability of deep nodes that divide aquatic and other early-diverging lineages within the Heteroptera, suggesting that some relationships remain difficult to resolve even with large amounts of data. In addition, despite the large amount of transcriptome data analyzed, quartet sampling revealed considerable underlying conflict for some nodes, even where bootstrap support is high, emphasizing the importance of considering multiple clade support values when analyzing phylogenomic datasets.